2014
DOI: 10.1007/s11182-014-0324-5
|View full text |Cite
|
Sign up to set email alerts
|

Charge Carrier Transport in LEDs Based on Multiple (Al x Ga1–x )0.5In0.5P/(Al0.54Ga0.46)0.5In0.5P Quantum Wells

Abstract: The results of experimental studies of forward current-voltage characteristics of LEDs with an active region consisting of the multiple (Al x Ga 1-x ) 0.5 In 0.5 P/(Al 0.54 Ga 0.46 ) 0.5 In 0.5 P quantum wells are presented. The experiment showed that increasing the number of quantum wells and decreasing the Al content in the Al x Ga 1-x solid solution lead to an increase in the forward current at a fixed voltage. An analysis showed that the results obtained can be interpreted using the theory of diffusion cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…This range of the forward CVC has n 0 ≈ 1 and n ≈ 1.3–1.5. Finally, in section III of the CVC a transition to the sublinear dependence in the semi‐log scale of the current vs the forward bias is observed in all investigated diodes . The increase in the QWs number from 10 to 20 in the LED leads to the growth of the forward current limitation at low temperatures, while at high temperatures it leads to the current density growth in section II of the CVC (inset in the Figure ).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…This range of the forward CVC has n 0 ≈ 1 and n ≈ 1.3–1.5. Finally, in section III of the CVC a transition to the sublinear dependence in the semi‐log scale of the current vs the forward bias is observed in all investigated diodes . The increase in the QWs number from 10 to 20 in the LED leads to the growth of the forward current limitation at low temperatures, while at high temperatures it leads to the current density growth in section II of the CVC (inset in the Figure ).…”
Section: Resultsmentioning
confidence: 75%
“…In the investigated diodes it was found that at the forward bias V < (1.6–1.8) V the j versus T obeys the exponential dependence with n 0 ≈ 2 and n ≈ 2. That current dominates in section I of the CVC in Figure and corresponds to the Shockley‐Read non‐radiative recombination . As the forward bias increases, the transition to the electroluminescence mode takes place that corresponds to the growth of the diode CVC characteristic slope (section II of CVC).…”
Section: Resultsmentioning
confidence: 98%